2017
DOI: 10.3390/ijerph14101270
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Early Feeding of Foods and Drinks Containing Free Sugars—A Birth Cohort Study

Abstract: Early feeding of free sugars to young children can increase the preference for sweetness and the risk of consuming a cariogenic diet high in free sugars later in life. This study aimed to investigate early life factors influencing early introduction of foods/drinks containing free sugars. Data from an ongoing population-based birth cohort study in Australia were used. Mothers of newborn children completed questionnaires at birth and subsequently at ages 3, 6, 12, and 24 months. The outcome was reported feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 42 publications
8
46
3
3
Order By: Relevance
“…We identified a diverse range of factors associated with the consumption of SSB by young children in LSIC, reflecting the complexity of factors influencing Aboriginal and Torres Strait Islander child nutrition (36) . In general, we observed lower SSB consumption prevalence among children whose families experienced socio-economic advantage, good life circumstances, and good health and well-being, broadly consistent with Australian and international evidence (1,19,42) . We observed differences between urban/inner regional and remote/outer regional settings in both the prevalence of SSB consumption and associated factors, demonstrating the importance of environmental and structural factors to children's nutrition.…”
Section: Overviewsupporting
confidence: 88%
See 1 more Smart Citation
“…We identified a diverse range of factors associated with the consumption of SSB by young children in LSIC, reflecting the complexity of factors influencing Aboriginal and Torres Strait Islander child nutrition (36) . In general, we observed lower SSB consumption prevalence among children whose families experienced socio-economic advantage, good life circumstances, and good health and well-being, broadly consistent with Australian and international evidence (1,19,42) . We observed differences between urban/inner regional and remote/outer regional settings in both the prevalence of SSB consumption and associated factors, demonstrating the importance of environmental and structural factors to children's nutrition.…”
Section: Overviewsupporting
confidence: 88%
“…While the present study indicates that SSB consumption is common among young Aboriginal and Torres Strait Islander children, this is not an issue specific to this population (18) ; there is clear evidence of a high prevalence of SSB intake among infants in the total Australian population (1,17,19,86) and in other countries including Finland (87) and Brazil (88) . Efforts to reduce SSB consumption by Aboriginal and Torres Strait Islander children could be broadened to lead to health benefits at the population level.…”
Section: Resultscontrasting
confidence: 61%
“…There were minimal missing data for sociodemographic variables, and no attempt was made to impute missing data. A previous sensitivity analysis for other dietary outcomes investigated in this cohort, in which missing data for sociodemographic explanatory variables was imputed under the assumption that data were missing at random, revealed that distributions of variables in the imputed data sets were consistent with the complete case data [38].…”
Section: Statistical Analysesmentioning
confidence: 70%
“…This could be related to type of foods or cooking methods preferred in each home country, which might contain hidden sugar. Our previous analysis of this same birth cohort reported substantial variation in the early introduction of foods and drinks high in free sugars, 30 with women who were born in other countries (particularly India) much more likely to do so than those born in Australia. Conditions which might restrict maternal time for caregiving (such as being a single and/or working mother or having more than one child) were not found in this study to be associated with ECC risk.…”
Section: Discussionmentioning
confidence: 76%